Subtle Signals of Status on Social Network Sites: Evidence From China - Wang, Wangshuai; Shao, Tiantian; Yi, Yanxi; Fang, Shijiao; Song, Jingyi; Yu, Zucheng (Frontiers in Psychology, 2021)
Social network sites (SNS) have been indispensable channels for people to access information, present themselves, and conduct commercial activities. Existing literature on online consumer behavior mainly focuses on Western consumers and on explicit conspicuous signals. However, reports have shown that SNS users in China have exceeded 370 million, ranking the first in the world. Meanwhile, nowadays more and more consumers display status in more implicit ways. To fill these gaps, the present research investigated the subtle signals of status for Chinese consumers on SNS. We proposed that frequent SNS posting leads to higher status perception among Chinese consumers. The psychological process of this effect is perceived busyness. These hypotheses received convergent support in a set of three studies. Study 1 used secondary data to preliminarily verify the positive correlation between SNS posting frequency and perceived social status. Study 2A and Study 2B adopted the causal chain method to test the underlying mechanism of the effect, and to provide causal evidence for the entire relationship chain. Specifically, Study 2A examined how SNS posting frequency affects perceived busyness. Furthermore, Study 2B explored whether the differences in perceived busyness will affect social status perceptions. Implications of these findings and potential extensions in future are discussed.